2013
DOI: 10.1007/s00454-013-9516-y
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and Diffraction of the $$k$$ k -Free Points in $$n$$ n -Dimensional Lattices

Abstract: Abstract. We consider the kth-power-free points in n-dimensional lattices and explicitly calculate their entropies and diffraction spectra. This is of particular interest since these sets have holes of unbounded inradius.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 19 publications
1
72
0
Order By: Relevance
“…Indeed, Schlottmann asks whether irregularity of the model set implies failure of unique ergodicity [24] and Moody has suggested that irregularity is related to positive entropy. The suggestion of Moody is recorded in [23] (later subsumed in [22]) and is also discussed in the introduction to [12]. When combined with examples of Toeplitz systems studied in the past, our main theorem allows us to answer these speculations by presenting model sets with various previously unknown features (such as irregularity combined with unique ergodicity and zero entropy).…”
Section: Consequences For Irregular Toeplitz Flowsmentioning
confidence: 88%
“…Indeed, Schlottmann asks whether irregularity of the model set implies failure of unique ergodicity [24] and Moody has suggested that irregularity is related to positive entropy. The suggestion of Moody is recorded in [23] (later subsumed in [22]) and is also discussed in the introduction to [12]. When combined with examples of Toeplitz systems studied in the past, our main theorem allows us to answer these speculations by presenting model sets with various previously unknown features (such as irregularity combined with unique ergodicity and zero entropy).…”
Section: Consequences For Irregular Toeplitz Flowsmentioning
confidence: 88%
“…In Ref. [2], it was shown that the above results remain true for the larger class of kth-power-free (or k-free for short) points of arbitrary lattices in n-space. Furthermore, it was shown there that these sets have positive patch counting entropy but zero measure-theoretical entropy with respect to a measure that is dened in terms of the`tied' frequencies of patches in space.…”
Section: Introductionmentioning
confidence: 86%
“…Since V ∈ A (otherwise some point of V is in p k Λ for some prime p, a contradiction) and since A is a Λ-invariant and closed subset of {0, 1} Λ , it is clear that X(V ) is a subset of A. By [2], Thm. 2, the other inclusion is also true.…”
Section: The Hull Of Vmentioning
confidence: 95%
See 2 more Smart Citations